2021
DOI: 10.3390/ebj2040019
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Responsiveness of and Defining Minimal Important Difference (MID) Values for the CARe Burn Scales: Patient-Reported Outcome Measures to Assess Quality of Life for Children and Young People Affected by Burn Injuries, and Their Parents/Caregivers

Abstract: The CARe Burn Scales are a portfolio of burn-specific PROMs for people affected by burns, including a Child Form (for children < 8 years (parent-proxy)), a Young Person Form (for young people aged 8–17 years), an Adult Form, and a Parent Form (for parents/carers of children aged 0–17 years). This study aimed to determine the responsiveness and minimal important difference (MID) values of the three scales developed for use in paediatric burn services and research. Participants were recruited by 15 UK Burn Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 61 publications
1
3
1
Order By: Relevance
“…In addition to less than one fifth suffered from associated illnesses with previous hospitalization (Table 1). These results cohort with the study of Griffiths et al, 2021 who detected that more than half of participants suffered from lateral burn injury. Also, it regulars with the study conducted in Nepal by Shrestha & Gurung, 2018 who concluded that the highest cause of burn among studied children was hot fluids burn.…”
Section: Discussionsupporting
confidence: 61%
“…In addition to less than one fifth suffered from associated illnesses with previous hospitalization (Table 1). These results cohort with the study of Griffiths et al, 2021 who detected that more than half of participants suffered from lateral burn injury. Also, it regulars with the study conducted in Nepal by Shrestha & Gurung, 2018 who concluded that the highest cause of burn among studied children was hot fluids burn.…”
Section: Discussionsupporting
confidence: 61%
“…For the overall questionnaire, higher scores indicate better outcomes. However, it appears that the scores for our patient cohort are lower than other values that have been published [12]. This was unexpected; given our cohort profile of non-severe burns, we expected that the scores would be similar to, or better than, published values.…”
Section: Discussioncontrasting
confidence: 46%
“…Second, the CARe Burn Scale (CARe) [12]: The CARe Burn Scale assesses the psychosocial effects of the burn scar on quality of life. This is a burn-specific questionnaire which takes about 15 min to complete.…”
Section: Methodsmentioning
confidence: 99%
“…However, they have not been routinely used in UK burn care [12], and the need for new PROMs to enable rigorous measurement was reinforced by the UK National Burn Care Standards [13]. We have therefore conducted a programme of work to develop and validate a portfolio of burn-specific age-appropriate PROMs, known as the CARe Burn Scales (Adult, Child, Young Person, and Parent Forms) [14][15][16]. These were created in accordance with a recognised, rigorous development and validation process [17] based on guidelines for the development of health outcome measures [18].…”
Section: Introductionmentioning
confidence: 99%
“…These were created in accordance with a recognised, rigorous development and validation process [17] based on guidelines for the development of health outcome measures [18]. This involved item generation through literature reviews, interviews with patients and health professionals, and a rigorous process of psychometric testing (using Rasch analysis) (see 14,15 for further details).…”
Section: Introductionmentioning
confidence: 99%